Hybrid Microstrip/Slotline Ultra-Wideband Bandpass Filter with a Controllable Notch Band - Xuehui Guan; Ping Gui; Tao Xiong; Baoping Ren; Lei Zhu (International Journal of Antennas and Propagation)
An ultra-wideband (UWB) bandpass filter (BPF) with a controllable notch band is presented by using hybrid microstrip/slotline structure. Firstly, a slotline resonator with symmetrically loaded stubs is fed by two microstrip lines to produce a UWB bandpass filtering response. Secondly, a microstrip triangular loop resonator is externally loaded over the slotline, and a notch band is introduced in the UWB passband. The notch band is determined by the perimeter of the loop resonator. Thirdly, two patches are added as the perturbation element to the corners of the microstrip resonator to excite a pair of degenerate modes. Bandwidth of the notch band can be tuned by properly selecting the patch size. Circuit model for the microstrip resonator loaded slotline is given and studied. Finally, the filter is designed, simulated, and measured. Measured results have agreed well with the simulated ones, demonstrating that a UWB filter with a controllable notch band has been realized.